1991
DOI: 10.1002/hlca.19910740837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N,N‐Disubstituted Lactone Hydrazones via (Sulfonylimino)‐ethers

Abstract: The dihydropyran 3 reacts with sulfonyl azides to give the known (sulfonylimino)‐ethers ( = lactone sul‐fonylimines) 4 and 18. Reaction of 4 with NH2NH2 · H2O leads to the aminoiriazole‐dibulanol 5, characterized as its tetraacetate 8, and not, as previously claimed, to 6 or 7. Similarly, the dihydrofuran‐derived (tosylimino)‐ether 10 yields 11 The structure of 5 was established by X‐ray analysis, and a mechanism for its formation is proposed. Reaction of 4 with NH2NMe2 afforded the lactone hydrazone 16 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…However, it was consistent with the observed diacetylation of 4-amino groups in related 1,2,4-triazoles reported by other research groups. [70,71] To obtain pure tetraacetate 20 in good yield it was crucial to reflux the reaction mixture vigorously and to immerse the reaction vessel in a preheated oil bath (160 8C) rather than increasing the temperature gradually. Inseparable mixtures of differently acetylated compounds were obtained when these directions were not followed.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was consistent with the observed diacetylation of 4-amino groups in related 1,2,4-triazoles reported by other research groups. [70,71] To obtain pure tetraacetate 20 in good yield it was crucial to reflux the reaction mixture vigorously and to immerse the reaction vessel in a preheated oil bath (160 8C) rather than increasing the temperature gradually. Inseparable mixtures of differently acetylated compounds were obtained when these directions were not followed.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Trifluoromethylsulfonyl Azide Solution: According to Fritschi and Vasella [28]. Synthesis of a-Nitro-a-diazo Esters 17.…”
Section: Experimental Partmentioning
confidence: 99%
“…We previously reported [27] a novel diazo-transfer reaction involving the treatment of a MeCN/hexanes solution of (trifluoromethyl)sulfonyl (trityl) azide [28] and an a-nitro ester or ketone with pyridine, which affords the corresponding a-nitro-…”
mentioning
confidence: 99%
“…The recently performed X‐ray analysis showed that it has a lamellar crystal structure with the distance between the layers of 3.4 Å . The X‐ray structure for complexes of triflamide with tetrahydro‐ N ‐(4 H ‐1,2,4‐triazol‐4‐yl)‐2 H ‐pyran‐2‐imine and 2,4,8,10‐tetraoxospiro[5.5]undecane was also determined …”
Section: Introductionmentioning
confidence: 99%